Diagnosis of Sepsis in Critically Ill Patients - M. L. Romasheva; D. G. Proshin (Общая реаниматология)
Objective: to ascertain the informative value of determining procalcitonin in the diagnosis of critical conditions and in the evaluation of the efficiency of performed therapy.Subjects and methods. Sixty patients aged 25—50 years (38.1±11.2 years) who had signs of the systemic inflammatory reaction syndrome, including 30 (50.0%) patients with severe sepsis, 21 (35.0%) with septic shock, 3 (5.0%) with meningitis of varying etiology, 2 (3.3%) with Candida infection, and 1 (1.7%) with vasculitis, and 3 (5.0%) with pulmonary thromboembolism, were examined. In all the patients, serum procalcitonin was determined by an RCTv-Q test (BRAHMS) in the first 24 hours of stay in an intensive care unit (ICU) and 72 hours after the initiation of multicomponent therapy.Results. Patients with severe sepsis and multiple organ dysfunction has a positive test with a plasma procalcitonin level of 2 ng/ml or higher in 100% of cases. In meningitis, the concentration of procalcitonin was 0.5 to 2 ng/ml; in Candida infection and thrombovasculi-tis, that was as high as 0.5 ng/ml. A negative test was obtained in pulmonary thromboembolism. Extracorporeal treatments (continuous venovenous hemodiafiltration on a PRISMA apparatus) were used as part of complex therapy in 14 patients with septic shock and multiple organ dysfunctions. In 9 (64.3%) of them, its concentration decreased to a varying degree, blood acid-base balance became normal, vital functions stabilized; 5 (13.5%) died.Conclusion. Procalcitonin is a highly specific marker of sepsis. In patients with severe sepsis, lower procalcitonin concentrations and septic shock suggests the efficiency of the performed therapy in this category of patients. Procalcitonin may be recognized to be a reliable parameter of the monitoring of not only the severity of bacterial infection, but also the evaluation of the efficiency of treatment in critically ill patients in an ICU.